PENGARUH PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) DAN MEDIA WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA SD INPRES PALOMPONG KABUPATEN GOWA - Mirwani; Sayidiman; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is an experimental research aimed at determining the effect of implementing the Teaching at the Right Level (TaRL) approach and Wordwall media on the IPAS learning outcomes of students at SD Inpres Palompong, Gowa Regency. The study employed a quantitative approach with an experimental research type. A quasi-experimental design was applied using a non-equivalent control group design. Research data were collected through observation sheets and tests. The population consisted of all students of SD Inpres Palompong totaling 217 students. The sample of this study was the fifth-grade students of SD Inpres Palompong, consisting of 45 students divided into two classes: class VA with 23 students and class VB with 22 students. Data analysis techniques included descriptive and inferential statistical analysis.The results of the study show: (1) a difference in IPAS learning outcomes between students taught using the Teaching at the Right Level (TaRL) approach and Wordwall media and those taught using conventional methods; (2) the effect of implementing the Teaching at the Right Level (TaRL) approach and Wordwall media on students’ IPAS learning outcomes at SD Inpres Palompong, Gowa Regency; and (3) the magnitude of the effect of implementing the Teaching at the Right Level (TaRL) approach and Wordwall media on students’ IPAS learning outcomes at SD Inpres Palompong, Gowa Regency.